Trade and Progress: The Case of China - Farah, Paolo Davide (Columbia Journal of Asian Law, 2016)
China's accession to the WTO is widely understood as an important step towards greater global market liberalization and integration. However, this step has been also perceived in an ambivalent way. On one hand, the global market liberalization would have never been really completed without participation of such a major player as China. On the other hand, many observers articulated concerns about China's ability to integrate into the WTO system. In order to tackle the issues of concern, attention was paid mainly to technical issues, which were seen as a precondition for China's successful integration into the WTO system. For this reason, topics related with market integration, such as e.g. liberalization requirements, as well as topics related with transparency and legal and administrative policies, necessary for securing of just and equitable resolution of commercial and trade disputes, were initially addressed. Still, in the light of the changing and evolving geopolitical climate, it has become more evident that Non-Trade Concerns (NTCs) might be another multifaceted topic requiring special attention. EU and US, becoming increasingly aware of the fact that competition of economies with different level of development might result not only in job losses in developed countries due to relocation of production, but also to general deterioration of environmental, social and health standards, have accentuated the importance of a global consensus on NTCs and their inclusion into EU and US external policies concerning foreign trade and investment. Civil society from the developed world, in general, is afraid that further liberalization may endanger public policies at different levels: environmental protection and sustainable development, good governance, cultural rights, labor rights, public health, social welfare, national security, food security, access to knowledge, consumer protection, and animal welfare. On the other hand, coalition consisting of China and other BRICS countries as well as other developing countries gaining more influence in the WTO and other international fora has been able to articulate discontent with measures adopted by developed countries to address NTCs. The clash between interests of developed and developing countries reveals potential unfairness and inconsistencies of the international system, including the international trade system, which needs to undergo a deep reform to integrate the developing countries' needs. Many of the measures that developed countries introduce to address NTCs were received by developing countries with suspicion, resistance, and even hostility. Developing countries, including China, doubt the authenticity of such considerations and think they might actually hide protectionist purposes. Additionally, developing countries see these measures as an indirect form of western imperialism whereby they will have no choice but to comply with the social, ethical, and cultural values of the developed states. Nonetheless, not only has China undergone serious reforms and adopted new regulations to address the issue of NTCs, but the country has even begun to play an important role in the international negotiations on NTCs-such as those on climate change, energy, culture, and so on. However, at the same time it provides an opportunity for China and other developing countries to defend their interests in a constructive dialogue with developed countries and restructure the system in order to find a necessary balance between globalization and sustainable development or to shape it according to their interests.